2013
DOI: 10.7567/apex.6.102101
|View full text |Cite
|
Sign up to set email alerts
|

GaN-Based Green-Light-Emitting Diodes with InN/GaN Growth-Switched InGaN Wells

Abstract: We have demonstrated the InN/GaN growth switching of the InGaN wells of green-light-emitting diodes (LEDs). The output power of green LEDs with InN/GaN growth-switched InGaN wells (120 mA) changed by approximately 23% compared with that of green LEDs with conventional InGaN wells. However, the emission wavelength blue shift and efficiency drops of green LEDs with InN/GaN growth-switched InGaN wells (15.0 nm and 44.6%, respectively) are larger than those of green LEDs with conventional InGaN wells (10.5 nm and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 31 publications
3
8
0
Order By: Relevance
“…That is, the linewidth locally recorded on one insertion is of a similar magnitude as the integral luminescence of planar QW structures [41,42]. Another observed feature is the emission at slightly higher energy than the main peaks visible in figures 6(d) and (f) between 2.5 and 2.8 eV.…”
Section: (Inga)n Luminescence Bandsupporting
confidence: 56%
See 2 more Smart Citations
“…That is, the linewidth locally recorded on one insertion is of a similar magnitude as the integral luminescence of planar QW structures [41,42]. Another observed feature is the emission at slightly higher energy than the main peaks visible in figures 6(d) and (f) between 2.5 and 2.8 eV.…”
Section: (Inga)n Luminescence Bandsupporting
confidence: 56%
“…For single (In,Ga)N insertions, Tourbot et al [18] observed an FWHM of 200 meV in TEM-based CL measurements, which is comparable to our results. That is, the linewidth locally recorded on one insertion is of a similar magnitude as the integral luminescence of planar QW structures [41,42]. Another observed feature is the emission at slightly higher energy than the main peaks visible in figures 6(d) and (f) between 2.5 and 2.8 eV.…”
Section: (Inga)n Luminescence Bandsupporting
confidence: 56%
See 1 more Smart Citation
“…The former can be explained by the screening effect of internal electric field, while the latter by the band filling effect. Generally, as the screening effect of the internal electric field in QWs dominates, the reduction of FWHM is accompanied 24 . The decreasing trend in FWHM was appeared to reduce more obviously from sample I to sample III, implying that the internal electric field in QWs decreases as d barrier decreases.…”
Section: Resultsmentioning
confidence: 99%
“…Elevating the growth temperature of GaN quantum barrier (QB) is found to be an effective way to improve the quality of active region [13]. Although the growth temperature of QB is usually 50-150 higher than that of QW, it is still [14,15], growth interruption [16,17] and indium treatment [18][19][20]. Recently, Ren et al demonstrated that full hydrogen treatment after GaN barrier layer growth can enhance both indium incorporation and quantum efficiency [21].…”
Section: Introductionmentioning
confidence: 97%